크리스토펠 기호

수학노트
http://bomber0.myid.net/ (토론)님의 2010년 1월 11일 (월) 14:59 판
둘러보기로 가기 검색하러 가기
  • 제1기본형식을 이용한 표현
    \(\Gamma^1_{11}=\frac{GE_u-2FF_u+FE_v}{2(EG-F^2)}\)
    \(\Gamma^1_{12}=\frac{GE_v-FG_u}{2(EG-F^2)}\)
    \(\Gamma^1_{22}=\frac{2GF_v-GG_u-FG_v}{2(EG-F^2)}\)
    \(\Gamma^2_{11}=\frac{2EF_u-EE_v-FE_u}{2(EG-F^2)}\)
    \(\Gamma^2_{12}=\frac{EG_u-FE_v}{2(EG-F^2)}\)
    \(\Gamma^2_{22}=\frac{EG_v-2FF_v+FG_u}{2(EG-F^2)}\)
  • \(F=0\) 인 경우
    \(\Gamma^1_{11}=\frac{GE_u-2FF_u+FE_v}{2(EG-F^2)}\)
    \(\Gamma^1_{12}=\frac{GE_v-FG_u}{2(EG-F^2)}\)
    \(\Gamma^1_{22}=\frac{2GF_v-GG_u-FG_v}{2(EG-F^2)}\)
    \(\Gamma^2_{11}=\frac{2EF_u-EE_v-FE_u}{2(EG-F^2)}\)
    \(\Gamma^2_{12}=\frac{EG_u-FE_v}{2(EG-F^2)}\)
    \(\Gamma^2_{22}=\frac{EG_v-2FF_v+FG_u}{2(EG-F^2)}\)